Regional integration, economic development and global governance - Volz, Ulrich; Edward Elgar Publishing (Cheltenham, Glos : Edward Elgar, 2011)
The contributors expertly provide a comparative perspective on regional integration in different regions of the world while at the same time analysing the various facets of integration, relating to trade, FDI, finance and monetary policies. They provide a comprehensive treatment of the subject and offer new perspectives on the potential developmental effects of regional integration and the implications of regional integration for global economic governance. Whilst highlighting and illustrating the potential benefits deriving from regional economic integration, the book also stresses the problems and challenges regional integration processes are usually confronted with.
pt. 1. Integration experiences in different regions -- pt. 2. Regional integration and the multilateral trading system -- pt. 3. Regional trade and foreign direct investment -- pt. 4. Regional financial integration -- pt. 5. Topics in monetary integration.
Includes bibliographical references and index.
Keywords: Economic development; International cooperation; Electronic books